Local scour at bridge piers in orifice flows - Wong, Chang Tai (Nanyang Technological University, 2021)
Climate change and global warming have been causing sea levels to rise with higher flood peak levels. The increasing flood levels has resulted in the damage of many bridges due to the flood waters exceeding the design parameters of the bridges. Existing bridges may experience pressurised flow conditions when water level reaches the bridge deck, causing increased scour at its foundations. This leads to bridge failures where the foundation is destabilised. In some cases, flood levels may even overtop a bridge, causing further damage to the structure. To resolve this situation, researchers have been studying the impact of flow conditions in order to mitigate the scour at the bridges’ foundations. Many studies have been done on open channel scour flow conditions. However, very few studies have included bridge piers in pressure scour conditions. In addition, while many experiments on debris accumulation have been carried out, there are not many studies linking debris accumulation with pressure scour flow conditions. Therefore, more emphasis are placed on local scour at bridge piers in orifice conditions in this study. All experiments were conducted in the NTU Hydraulics Modelling Lab. Four variations of the bridge deck were used to study its effect on scour depth. Flow conditions were kept constant throughout the experiment, where the only change is the streamwise position of the bridge deck. Results showed that orifice conditions produce 10% increase in scour depth when compared to open channel flow. It is also found that the length between the edge of the bridge deck to the pier centre, or overreach length, plays a limiting role in the scour depth, where the ratio of the overreach length to the pier diameter results in maximum scour when the ratio equals to 3, and any increase or decrease to that ratio results in reduced scour.